1999
DOI: 10.1093/hmg/8.9.1621
|View full text |Cite
|
Sign up to set email alerts
|

ATP2A2 Mutations in Darier's Disease: Variant Cutaneous Phenotypes Are Associated with Missense Mutations, But Neuropsychiatry Features Are Independent of Mutation Class

Abstract: Darier's disease (DD) is an autosomal dominant skin disorder characterized clinically by multiple keratotic papules, and histologically by focal loss of adhesion between epidermal cells (acantholysis) and by abnormal keratinization. Variant forms of cutaneous phenotype, sometimes familial, have been described. Associated neuropsychiatric features, including mental handicap, schizophrenia, bipolar disorder and epilepsy, have also been reported. The cause of DD was shown recently to be mutation in the ATP2A2 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
154
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(165 citation statements)
references
References 42 publications
8
154
1
2
Order By: Relevance
“…Most physiological systems are able to compensate for the loss of function of SERCA2b, possibly because of expression of other SERCA isoforms within those tissues (Dhitavat et al, 2003;Tavadia et al, 2004). However, of the multiple isoforms of SERCA1, -2, or -3, only SERCA2b is expressed in keratinocytes (Lytton and MacLennan, 1988;Ruiz-Perez et al, 1999). The mutated SERCA2 fails to sequester cytosolic Ca 2ϩ into the endoplasmic reticulum (ER) lumen, thereby disturbing the otherwise normal Ca 2ϩ homeostasis circuitry within the cells (Zhao et al, 2001;Ahn et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Most physiological systems are able to compensate for the loss of function of SERCA2b, possibly because of expression of other SERCA isoforms within those tissues (Dhitavat et al, 2003;Tavadia et al, 2004). However, of the multiple isoforms of SERCA1, -2, or -3, only SERCA2b is expressed in keratinocytes (Lytton and MacLennan, 1988;Ruiz-Perez et al, 1999). The mutated SERCA2 fails to sequester cytosolic Ca 2ϩ into the endoplasmic reticulum (ER) lumen, thereby disturbing the otherwise normal Ca 2ϩ homeostasis circuitry within the cells (Zhao et al, 2001;Ahn et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, our findings shed light on coordinated cross talk among protein, redox, and calcium homeostasis, which are three major types of homeostasis in the ER. Darier's disease, an autosomal dominant inherited disorder of the skin, was reported to be caused by an anomaly of Ca 2+ signaling due to mutations of SERCA2b (29)(30)(31)(32). Because of lossof-function mutations in SERCA2b, keratinocytes in Darier's disease patients were reported to have a reduced pool of Ca 2+ in the ER.…”
Section: Discussionmentioning
confidence: 99%
“…26 A variety of missense, nonsense, frameshift and splicing mutations in the ATP2A2 gene have been identified in familial Darier's disease, an autosomal skin disorder, demonstrating that this gene is closely related to this disease. [12][13][14] Interestingly, some patients with Darier's disease (30 -50%) have OPLs (hyperkeratosis). 29,30 However, in vitro studies showed that the calcium content of the ER lumen is a key determinant in the control of apoptosis induced by physiologic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of each primer and each PCR condition was based on those reported previously. 13 After amplification, PCR products were electrophoresed on 10% polyacrylamide gels under several different conditions at 4°C, 15°C and room temperature. After electrophoresis, the gel was silver-stained using the DNA Silver Staining Kit (Amersham, Piscataway, NJ).…”
Section: Mutational Analysesmentioning
confidence: 99%
See 1 more Smart Citation